2020
DOI: 10.1016/j.envpol.2020.115131
|View full text |Cite
|
Sign up to set email alerts
|

The factors associated with distress following exposure to smoke from an extended coal mine fire

Abstract: In February 2014, the coalmine adjacent to the Hazelwood Power Station in the Latrobe Valley of Victoria, Australia, caught fire, with residents from the nearby town of Morwell and the wider area exposed to smoke for six weeks. Although there was evidence linking the mine-fire event with psychological distress, no studies have evaluated the degree of distress in relation to the level of smoke exposure. We aimed to investigate the exposure-response relationship between particulate matter 2.5μm or less in diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The impact of the mine fire on academic performance may be due to numerous factors, including disruption to day-to-day operations, 22 traumatic symptoms caused by the mine fire, 37 known associations between air pollution and impaired cognitive function, 38,39 adverse physical health effects of exposure to the Hazelwood mine fire-related air pollution (e.g. respiratory symptoms), 40 ongoing distress experienced by students, teachers and parents 22,41,42 and possibly reduced support from family and community. Given academic underachievement can lead to unemployment, disadvantage and ill-health later in life, 43 it is critical that these impacts are recognised and responded to.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The impact of the mine fire on academic performance may be due to numerous factors, including disruption to day-to-day operations, 22 traumatic symptoms caused by the mine fire, 37 known associations between air pollution and impaired cognitive function, 38,39 adverse physical health effects of exposure to the Hazelwood mine fire-related air pollution (e.g. respiratory symptoms), 40 ongoing distress experienced by students, teachers and parents 22,41,42 and possibly reduced support from family and community. Given academic underachievement can lead to unemployment, disadvantage and ill-health later in life, 43 it is critical that these impacts are recognised and responded to.…”
Section: Discussionmentioning
confidence: 99%
“…Two schools were relocated causing direct educational interruptions as well as threats to student’s sense of safety and security (Berger et al, 2018). The mine fire also led to ongoing distress experienced by students, teachers and parents in the smoke affected community post the mine fire (Berger et al, 2018; E. Berger, Maybery, et al, 2020; Broder et al, 2020; Maybery et al, 2020). Hazelwood mine fire-related air pollution has also been linked to a range of adverse physical health effects such as respiratory morbidity (Gao et al, 2020; Holt et al, 2021; Johnson et al, 2019; Shao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is evidence that older people may be more likely to have health impacts as a result of disasters, there is a growing body of literature suggesting the reverse may be the case for psychological impacts. A recent finding from the Hazelwood Health Study, which is looking at the impacts of an extended pollution event on the health of residents in a Victorian regional community, found that older people were less likely to report distress associated with exposure to the event compared with younger people 7 . This finding is in line with other disaster research, which suggests that older people may be more psychologically resilient, possibly because of having responded to and learned from previous traumatic events across their longer lifespans.…”
mentioning
confidence: 99%